The effect of a cognitive or motor task on gait parameters of diabetic patients, with and without neuropathy - Paul, L.; Ellis, B. M.; Leese, G. P.; McFadyen, A. K.; McMurray, B. (Diabetic medicine, 2009)
Aims  To compare gait parameters of older people with diabetes and no peripheral neuropathy (DM) and people with diabetes and diabetic peripheral neuropathy (DPN) and to investigate the effect of a secondary motor or cognitive task on their gait. Methods  Thirty subjects were recruited: 15 with DPN (mean age 69 ± 3.0 years) and 15 with diabetes and no neuropathy (70 ± 2.9 years). The temporal and spatial parameters of gait were determined using the GAITRite walkway. Subjects undertook four walks: under normal walking conditions (single task); four times while simultaneously undertaking an additional motor task, carrying a tray with cups of water (dual task); and four times whilst undertaking a cognitive dual task, counting backwards in sevens. This arithmetic task was also completed sitting. Results  For all gait variables, there was a statistically significant difference between the groups. Subjects with DPN walked more slowly and with smaller steps compared with those with DM. In general, the secondary task had a significant and adverse effect on the gait parameters and this effect was greater for those with DPN in both absolute and relative terms. Both groups had poorer arithmetic ability when walking compared with sitting. Discussion  Patients with DPN have different gait parameters to diabetic patients without neuropathy. Problems with divided attention when walking were more evident in the DPN group and may increase their risk of falls.